Jual Beli Harta Benda Wakaf Menurut Madzhab Syafi’i: Studi Analisis Pemikiran Ibnu Hajar al-Haitami - Nurhasanah .; Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The problem of this study is how the purchase procedure of wakf property according to the school of Shafi’i jurisprudence, focusing on the thought of Ibn Hajar al-Haytami? The conclusion of this study, Ibn Hajar al-Haytami is one of the followers of Shafi'i’s school of fiqh, (Islami jurisprudence) and he expressly prohibit the sale and purchase of wakf property under any circumstances. According to Al-Haitami property of wakf had broken up his property and belong to Allah. Therefore, property of wakf has not be authorized for sale in the all condition. There is possibility when he banned the sale and purchase of the wakf property, affected by the state of Muslims who was very much with the teachings of Islam or Al-Haitami’s thought of fiqh. Although prohibits selling property of wakf, it allows rent it. The wakf has been relevant to the development of society, especially for Muslims of Indonesia, such as the development of the construction and rental of flats on wakf land, as it has been regulated in the management of productive of wakf in the legislation of wakf.